Land artificialization, economic growth, and road insecurity: Theoretical improvements and empirical validation for the case of Algeria - Riadh, Harizi (Technium Social Sciences Journal, 2021)
This paper applies the Kuznets (1955) curve approach to road traffic crashes in Algeria based on active population, motorization rate, income per capita, and land artificialization. It aims to establish a link between economic development and road safety by estimating the terms of quadratic equations related to the occurrence of traffic collisions. The results reveal that a link between economic development and road safety can be validated by two econometric specifications for the Kuznets curve (KC). Indeed, because economic conditions remained favorable, the Algerian economy reached its inflection point in 2011 and then entered the second phase of the KC. The increase in the level of economic development then in turn led to an improved road-safety situation in terms of lower mortality rates on the roads.